The Social Contexts of Birthing People with Public- and Private-Payer Prenatal Care: Illuminating an Understudied Aspect of the Patient Experience (Mary Ann Liebert, 2022)
Purpose: In pursuit of more equitable and person-centered health care, patients and professional medical societies increasingly call for better clinician understanding of patients' perspectives and social contexts. A foundational but understudied aspect of patients' social contexts are the ideas they encounter about health-related behaviors. We investigated this aspect of the social contexts of birthing people, comparing those with public versus private insurance to discover setting-specific insights. Methods: Based on ethnographic fieldwork, we created an original survey featuring 29 statements about 12 prenatal, perinatal, and postpartum health behaviors (e.g., drinking alcohol, epidural use, breastfeeding). Participants were 248 individuals receiving prenatal care in Northern California in 2009?2011, split evenly between public- and private-payer coverage. Participants reported whether they were familiar or unfamiliar with each statement. Results: Ninety-eight percent of all participants had heard contradictory ideas about ?1 health behavior (mean=3.9 behaviors for public- and 5.4 for private-coverage respondents). For 20 of the 29 behavior-related ideas, exposure varied significantly by coverage type. Among other differences, public-coverage respondents were much more familiar with ideas related to risk and constrained autonomy (e.g., that serious perinatal complications are common; that new mothers should try to breastfeed even if they do not want to). Conclusions: Birthing people are exposed to a wide range of ideas about health behaviors, many of which vary by the structural systems in which they are embedded. Understanding and engaging this complexity can help clinicians to provide more respectful, person-centered, and equitable maternity care.